Riverine Mg isotopes response to glacial weathering within the Muztag catchment of the eastern Pamir Plateau. (July 2020) - Li, Liangbo; Zhang, Fei; Jin, Zhangdong; Xiao, Jun; Gou, Long-Fei; Xu, Yang
Abstract: It has been proposed that the riverine Mg isotopes are sensitive to primary mineral dissolution and the formation of secondary minerals and are served as an effective tracer for chemical weathering. Glacial comminution can produce fresh mineral surfaces that provide easily leached cations to the rivers and thus could potentially modify the riverine Mg isotopic behavior. However, the mechanism controlling riverine Mg isotopes under glacial environment is poorly constrained. Here we investigated Mg and Sr isotopic compositions of river and spring waters, bedrocks and sediments within the glacial-covered Muztag catchment in the northeastern Pamir Plateau. The δ 26 Mg and 87 Sr/ 86 Sr values of dissolved loads along the mainstream increased from −1.56‰ and 0.713050 at the glacier margin to −1.12‰ and 0.713855 at the downstream, respectively, both showing strong negative correlation with elevation. The lower δ 26 Mg but higher molar Ca/Mg and Ca/Na ratios of glacial river waters than those of non-glacial rivers indicate a preferential dissolution of carbonates under glacial environment, further supported by a negative liner correlation between δ 26 Mg and carbonate weathering proportion. In contrast, the high δ 26 Mg but low Ca/Mg and Ca/Na ratios at the downstream reflect an increased input of silicate weathering. Saturation state modelling suggests little chance of secondary mineral formation and limited impact on the Mg isotopic behavior in glacial rivers, characterized by low ionic concentrations and short water residence time. These observations, together with complied data from other glacial rivers, suggest preferential carbonate weathering under glacial environment could directly release low Mg isotopes to river water, different from the process of Mg isotopic fractionation by secondary mineral formation. Our findings would provide insight in carbonate weathering regulating riverine Mg isotopic evolution and its potential influence on global carbon cycle, in particular under present warming scenario. Highlights: Riverine Mg isotopic compositions in the extremely dry and cold northeastern Pamir Plateau were firstly investigated. Preferential carbonate weathering under glacial environment impacts riverine Mg isotopes. Enhanced dissolution of carbonates by glacial comminution at basin scales. The significant impact of carbonate weathering on river chemistry and Mg isotopes in alpine glacial regions..